ALAT BANTU PENDINGINAN FILTER OLI MOBIL - Taufiq Hidayat (TRAKSI, 2019)
The main function of an oil filter in a car is to filter the oil coming from the charter to be circulated to the engine. The main function of the oil between it is as a lubricant and engine coolant. The engine working temperature is affected by the engine cooling system and the oil function which acts as a cooler. One effort to improve the quality of oil cooling can be done with the addition of cooling aids placed in the oil filter. The purpose of this research is to determine the effectiveness of changes in the working temperature of the engine mounted cooling aids on oil filters. The method used to conduct research is the use of metal and aluminum based tools with the number of fins that are varied. The shape of the tool is a metal sleeve with fin fins that vary in number. The results of the temperature scale under the influence of engine speed in this study is the greatest level of decline with variations in the number of fins of 10oC. Whereas with the use of different materials, a 5oC reduction was obtained in the use of aluminum compared to stainless steels.